NIKA2 observations of dust grain evolution from star-forming filament to T-Tauri disk: Preliminary results from NIKA2 observations of the Taurus B211/B213 filament - Nguyen-Luong Q.; Adam R.; Ade P.; Ajeddig H.; André P.; Artis E.; Aussel H.; Beelen A.; Benoît A.; Berta S.; Bing L.; Bourrion O.; et al. (EPJ Web of Conferences, 2024)
To understand the evolution of dust properties in molecular clouds in the course of the star formation process, we constrain the changes in the dust emissivity index from star-forming filaments to prestellar and protostellar cores to T Tauri stars. Using the NIKA2 continuum camera on the IRAM 30 m telescope. we observed the Taurus B211/B2I3 filament at 1.2 mm and 2 mm with unprecedented sensitivity and used the resulting maps to derive the dust emissivity index β. Our sample of 105 objects detected in the β map of the B211/B213 filament indicates that, overal. β decreases from filament and prestellar cores (β ~ 2 ± 0.5) to protostellar cores (β ~ 1.2 ± 0.2) to T-Tauri protoplanetary disk (β < I). The averaged dust emissivity index β across the B211/B2I3 filament exhibits a flat (β ~ 2 ± 0.3) profile. This may imply that dust grain sizes are rather homogeneous in the filament, start to grow significantly in size only after the onset of the gravitational contraction/collapse of prestellar cores to protostars, reaching big sizes in T Tauri protoplanetary disks. This evolution from the parent filament to T-Tauri disks happens on a timescale of about 1-2 Myr.